Codes over M2(F2) and applications to golden space-time coded modulation - Oggier, Frederique (2009)
In this paper, we study code constructions over the finite ring M2(F2), the ring of 2 x 2 matrices with coefficients in the finite field F2. We show how they can be related to classical codes over F4. We provide as application the design of outer codes for 2 x 2 space-time coded modulation, when the inner code is the so-called Golden code.